2018
DOI: 10.3389/fped.2018.00408
|View full text |Cite
|
Sign up to set email alerts
|

ExtraUterine Growth Restriction (EUGR) in Preterm Infants: Growth Patterns, Nutrition, and Epigenetic Markers. A Pilot Study

Abstract: Background/Aims: IntraUterine (IUGR) and ExtraUterine Growth Restriction (EUGR) may induce reprogramming mechanisms, finalized to survive before and after birth. Nutritional factors and other environmental signals could regulate gene expression through epigenetic modification, but the molecular mechanisms involved are not yet well understood. Epigenetic mechanisms could be considered as a bridge between environmental stimuli and long lasting phenotype, acquired during the intrauterine life and the first weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
0
17
0
5
Order By: Relevance
“…The high incidence of EUGR reveals the challenging nature of the nutritional status of VLBWIs in China during hospitalization [9]. The lower the gestational age, the lower the birth weight and the higher the incidence of EUGR [10]. In this study, the incidence of EUGR is signi cantly lower, which may be due to the small sample size or better NICU preterm infant management.…”
Section: Discussionmentioning
confidence: 64%
“…The high incidence of EUGR reveals the challenging nature of the nutritional status of VLBWIs in China during hospitalization [9]. The lower the gestational age, the lower the birth weight and the higher the incidence of EUGR [10]. In this study, the incidence of EUGR is signi cantly lower, which may be due to the small sample size or better NICU preterm infant management.…”
Section: Discussionmentioning
confidence: 64%
“…19 In a recent report from Italy, EUGR was diagnosed in 71% and 50% of less than 34-week infants based on weight and head circumference at discharge, respectively. 12 One of the main factors for development of EUGR is the inadequate nutritional status at birth. The rate of EUGR among SGA infants included in our study was 97% (70 out of 72) compared with 73% (128 out of 175) in non-SGA.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include antenatal growth status, postnatal nutritional support, co-morbidities, and genetic and epigenetic factors. 12,13 Studies have shown that the risk of EUGR increases with decreasing birth weight and gestational age and is more obviously seen in the more mature SGA infants. 13 Another factor that affects the risk of EUGR is the duration of initial weight loss in the neonatal period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, EUGR is still a serious problem for ≤ 34w preterm infants, and the risk factors leading to EUGR include gestational age, birth weight, BPD, and SGA (7,33) . Previous studies reported that the EUGR incidence of preterm infants with gestational age ≤ 32w was 57%-71% (33)(34)(35)(36) , and Chinese studies reported that the incidence of EUGR in preterm infants with birth weight ≤ 1200 g was 83.8% (37) . In this literature, the overall survival rate of ELBW infants was higher than the domestic level, but approximately 2/3 of ELBW infants suffered from GR, de ned as the decline of Z score more than one.…”
Section: Risk Factors Of Growth Retardation During In-patient Periodmentioning
confidence: 99%